The underlying difference of metastatic and non-metastatic breast cancer cells in configuring type I collagen fibres to promote migration by cell mechanics - Mingxing Ouyang; Weihui Chen; Ting Zhou; Hongjie Liu; Lei Liu; Bing Bu; Linhong Deng (Mechanobiology in Medicine)
The progression of tumors is heavily influenced by mechanical properties of their microenvironment. In this work, we applied micropatterned models with varying distances and shapes to investigate the differences between metastatic MDA-MB-231 and non-metastatic MCF-7 breast cancer cells in reconfiguring extracellular matrix to promote cell migration induced by cell mechanics. Both cancer cells were able to rearrange type I collagen (COL) to form fibre threads, in which MDA-MB-231 consistently migrated more rapidly than MCF-7, ranging from geometrical square arrays with different spacings to complex polygonal models. MDA-MB-231 displayed higher capability of reorganizing fibre bundles at longer distance (800 ​μm). Further looking for differences in cell molecular mechanisms, siRNA knockdown inhibiting either integrin β1 or Piezo1 decreased fibre assembly and reduced the difference in COL remodeling and migration between two cancer cells. MDA-MB-231 showed inhibited migration with integrin knockdown, whereas scattering migration with Piezo1 knockdown, indicating cells losing directional mechanosensation. After inhibiting junctional E-cadherin with siRNA, MCF-7 cells migrated faster, resulting in reduced difference in comparison to MDA-MB-231 that didn't express E-cadherin. In summary, this work has explored the biomechanical differences between metastatic and non-metastatic breast cancer cells regarding COL fibre matrix remodeling and cell movements. The significant differences in E-cadherin expression in the two breast cancer cells had an effect on cell migrations. The results of this study provide research approaches for evaluating therapeutic effort on breast cancer.